Some Fixed Point Results for Perov-Ćirić-Prešić Type F-Contractions with Application. (28th August 2020) - Gholidahneh, Abdolsattar; Sedghi, Shaban; Parvaneh, Vahid
Abstract : Ćirić and Prešić developed the concept of Prešić contraction to Ćirić-Prešić type contractive mappings in the background of a metric space. On the other hand, Altun and Olgun introduced Perov type F-contractions. In this paper, we extend the concept of Ćirić-Prešić contractions to Perov-Ćirić-Prešić type F-contractions. Our results modify some known ones in the literature. To support our main result, an example and an application to nonlinear operator systems are presented.